El souvenir religioso desde la oferta y la demanda en la romería de la Virgen de El Cisne - Román Aguilar, Carla Victoria (2018)
Abstract:The pilgrimage of the Virgin of El Cisne is one of the biggest manifestations of faith in the country, which with the course of the years is kept strongly deep-rooted, congregating every year to thousands of devout that come as sample of his religiousness. Before the raised context there is generated great development of the commercial activity and focusing concretely in the topic of study, the great abundance of pilgrims carries to the demand of souvenirs religious of the Virgin all the year. By it diversity of religious objects they are commercialized, from principally of countries as Peru and Colombia, whereas in minor proportion products elaborated in the zone are offered, since the local craftsman in the main is not focused in the manufacture of this type of souvenirs. With the described proposal one tries to satisfy principally the needs of the pilgrims and on the other hand to stimulate to the local craftsman in the production of souvenirs religious that would allow him to be inserted in another area of market, improving his quality of life with the generation of a new source of income.